Analysis of matK and trnL-trnF Intergenic Spacer on Pandan (Benstonea sp.) From Kualu Village, Riau Province, Indonesia - Nugraha, Fadel; Sofhya, Putri Tri; Putri, Fatma Jumaita; Herman, Herman; Roslim, Dewi Indriyani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Molecular characterization using DNA barcodes is essential for clarifying taxonomic relationships and confirming species identity within the genus Benstonea. Pandan (Benstonea sp.) has potential as a source of bioactive compounds, a subject of genetic and taxonomic studies, and a component of biodiversity that supports conservation and the development of tissue culture for secondary metabolite production. This study aims to analyze the DNA barcode regions matK and trnL-trnF intergenic spacer (IGS) on Benstonea sp. collected from Kualu Village, Riau Province, Indonesia. The fresh leaves of this plant were used for DNA extraction using the Geneaid Mini Plant kit, PCR following Thermo Scientific protocols, agarose gel electrophoresis, sequencing, and data analysis using BioEdit, BLASTn, and MEGA 11.0. In this study had been obtained DNA sequences of matK and trnL-trnF IGS with the size of 846 bp and 964, respectively. Based on BLASTn analysis of the sequences, it showed that the pandan species originating from Kualu Village (Kampar Regency) and Langgam Village (Pelalawan Regency) have similarities with accessions from other genera of the Pandanaceae family (average query cover value reaches 100%). Phylogenetic analysis of the trnL-trnF IGS showed that the pandan plants studied were in the same group as Benstonea sp. 'Kajuik Lake' DIR01 and were clearly separated from the Pandanus and Martellidendron groups. The trnL-trnF IGS can be used to differentiate and group species of the genera Benstonea and Pandanus into distinct clades, whereas the matK was only effective for classification at the genus level. The sequences were submitted to GenBank and were available for use in the molecular identification of this plant.